2D SnSe2 micro-flower decorated with 0D In2O3 nanoparticles for low-temperature low-concentration TEA detection - Li Wang; Jianpeng Li; Cheng Xu; Ziqin Yang; Xiangyun Tan; Zhihu Dong; Li Xu; Dongwei Zhang; Chunqing He (Nano Materials Science)
Triethylamine, a crucial industrial raw material, poses significant threats to both the ecosystem and human health. However, detecting lower concentrations of TEA remains an arduous task. In this study, we report the facile hydrothermal and ultrasonic treatment synthesis of 2D SnSe2 micro-flower modified with 0D In2O3 nanoparticles to form SnSe2/In2O3 heterojunctions for the first time. The SnSe2/In2O3 sensor has a response value of 4.86 for 10 ​ppm TEA gas at 120 ​°C, with response and recovery times of 18 ​s and 79 ​s respectively, and detection limits as low as 100 ​ppb. In addition, the SnSe2/In2O3 sensor is essentially unaffected by humidity in the 30% RH to 60% RH range, and the SnSe2/In2O3 sensor response value decreases slightly in the 70% RH to 97% RH range, demonstrating excellent humidity tolerance. More importantly, the sensor maintained excellent cyclic-stability performance during a four-month cyclic stability test. The improved gas-sensitive performance can be attributed to the large number of n-n heterojunctions in the SnSe2/In2O3 material, which enhances the interfacial charge transfer, as well as the active-sites on the material surface. This work serves as a valuable complement to the TEA gas sensor and holds significant potential for detecting low concentrations of TEA at low temperatures in environmental sensing applications.